Pedagogical Communication and its Importance - Yuldasheva Farogat Turakulovna; Bazarova Shohida Ashirkulovna (Zien Journals, 2022)
Communication is manifested in conjunction with the social needs that arise as a result of the spiritual basis of human activity. It also has a significant impact on the formation of interpersonal relationships, the culture of communication. Consequently, communication takes a leading place among the activities carried out among people, it satisfies the most important needs of a person in relation to living in society and considering himself as an individual. That is why it is so important for everyone. ”[1] Communication is the process by which people interact with each other through various activities that arise from their joint activities, their needs.
Keywords: Communication; culture; person; society